2019
DOI: 10.31616/asj.2018.0234
|View full text |Cite
|
Sign up to set email alerts
|

Locking Stand-Alone Cage Constructs for the Treatment of Cervical Spine Degenerative Disease

Abstract: Study Design Prospective case series study. Purpose Description of the outcome of stand-alone cervical cages for single and multilevel cervical degenerative spine disease. Overview of Literature The aim of anterior cervical discectomy and fusion (ACDF) for cervical spine disease is to improve patient symptoms and spine stability and restore lordosis. Locking stand-alone cages were developed with the goal of minimizing soft tissue disruption a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Using a more lenient cutoff of 4 degrees or less of angular motion to assess fusion status, we found that 82.5% of levels would meet this criteria. Using stringent radiographic criteria to assess for fusion status, the observed fusion rate was lower than previously reported literature fusion rates of 84%-96% [30][31][32]. While it is important to report short term radiographic data, it is unclear whether the observed fusion rate is clinically significant.…”
Section: Discussionmentioning
confidence: 60%
“…Using a more lenient cutoff of 4 degrees or less of angular motion to assess fusion status, we found that 82.5% of levels would meet this criteria. Using stringent radiographic criteria to assess for fusion status, the observed fusion rate was lower than previously reported literature fusion rates of 84%-96% [30][31][32]. While it is important to report short term radiographic data, it is unclear whether the observed fusion rate is clinically significant.…”
Section: Discussionmentioning
confidence: 60%
“…ACDF has been one of the standard treatments for cervical spondylopathy since it was rst described in the 1950s [16,17]. For multilevel lesions, although many prefer the posterior approach to achieve broader indirect decompression[18], the anterior approach has the characteristic of direct decompression of the neurological structures, less interference with posterior muscles, and hence less surgical trauma [19][20][21][22]. As experience with the anterior cervical plate has accumulated, the advantages of an enhanced fusion rate, better cervical spine realignment, and lordosis maintenance have been proven [23].…”
Section: Discussionmentioning
confidence: 99%
“…APC as the standard technique in ACDF is effective in maintaining cervical stabilization, improving cervical lordotic alignment, preventing cage dislocation, and increasing fusion rates. Previous studies showed the efficacy and safety of using ACDF with cage and plate for signal level or multilevel patients with cervical spondylotic conditions ( 15 , 17 ). However, increased complication rates associated with plate fixation have been reported in patients with multilevel ACDF ( 15 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed the efficacy and safety of using ACDF with cage and plate for signal level or multilevel patients with cervical spondylotic conditions ( 15 , 17 ). However, increased complication rates associated with plate fixation have been reported in patients with multilevel ACDF ( 15 , 17 ). In order to overcome these complications, stand-alone cages were developed and used.…”
Section: Discussionmentioning
confidence: 99%